Safe aging - Mohammad Alkhateeb; Ahmad Hawwari (My University, 2025)
In this era of technological advancements, applications and software have become essential in people's lives, facilitating the fulfillment of their needs and addressing various matters. Our focus has been directed toward the elderly, considering the challenges they face in frequent mobility and the necessity of monitoring their health conditions regularly with specialized doctors. Therefore, we developed this project aimed at tracking the health status of senior citizens by enabling their communication with doctors through our dedicated application. Each patient can connect with one or more doctors as needed , monitor their medical reports , manage their prescribed medications and schedules, and facilitate communication during emergencies . The application also allows patients to schedule follow-up appointments, access information about hospitals and doctors, and provides a comprehensive directory of healthcare providers.